2015
DOI: 10.1186/s12906-015-0920-0
|View full text |Cite
|
Sign up to set email alerts
|

Activity guided isolation and modification of juglone from Juglans regia as potent cytotoxic agent against lung cancer cell lines

Abstract: BackgroundJuglans regia has been found to exhibit significant anticancer activity against various human cancer cell lines. This study was undertaken to isolate the active chemical constituent (Juglone) and to investigate its cytotoxic activity along with its various analogs against different human cancer cell lines.MethodsIsolation of juglone, a napthoquinone, from the chloroform extract of the root part of Juglans regia was executed by flash chromatography using silica gel as stationary phase. The isolated Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 32 publications
0
28
0
2
Order By: Relevance
“…as STAT3 signaling inhibitors [14] and found that 2-methoxystypandrone inhibited both STAT3 and NF-κB pathways dramatically by inhibiting Janus kinase 2 (JAK2) and IκB kinase (IKK) [15]. Juglone analogues have been isolated from numerous medicinal plants as active constituents, which exhibited many biological activities such as anti-viral, anti-bacterial, anti-inflammatory, and anti-cancer activities [16, 17]. Because of an interest in juglone analogues with STAT3 pathway inhibitory activities, the EtOAc extract of the roots of P. cuspidatum was re-examined and a novel juglone analogue 2-ethoxystypandrone (1) along with seven known compounds (2–8) were isolated.…”
Section: Introductionmentioning
confidence: 99%
“…as STAT3 signaling inhibitors [14] and found that 2-methoxystypandrone inhibited both STAT3 and NF-κB pathways dramatically by inhibiting Janus kinase 2 (JAK2) and IκB kinase (IKK) [15]. Juglone analogues have been isolated from numerous medicinal plants as active constituents, which exhibited many biological activities such as anti-viral, anti-bacterial, anti-inflammatory, and anti-cancer activities [16, 17]. Because of an interest in juglone analogues with STAT3 pathway inhibitory activities, the EtOAc extract of the roots of P. cuspidatum was re-examined and a novel juglone analogue 2-ethoxystypandrone (1) along with seven known compounds (2–8) were isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Juglone, a naphthoquinone, isolated from Juglans regia is a potential cytotoxic compound against human lung cancer cell lines, and the electron-withdrawing groups at the ortho position of the R moiety of juglone seem to be necessary for the enhancement of its cytotoxic activity [24].…”
Section: Quinonoids Inhibit Proliferation and Induce Apoptosismentioning
confidence: 99%
“…Juglone ( Figure 1 ) is a member of this family, acting as a growth-stunting agent [ 136 ] and apoptosis inducer. It exhibits antitumour activity on many types of tumours, such as breast [ 92 , 93 , 94 , 95 , 137 ], skin [ 99 , 100 , 137 ], glial cells [ 109 , 110 , 111 , 135 , 138 ], lung [ 137 , 138 ], prostate [ 105 , 106 , 107 , 137 ], pancreas [ 97 ], bladder [ 108 ], stomach [ 98 ], cervix [ 102 , 103 , 139 , 140 ], ovary [ 104 ], and blood [ 113 , 114 ]. For some of them, the mechanism of action has been investigated.…”
Section: Anticancer Activitymentioning
confidence: 99%